Savitzky-Golay Filter-Based PLL: Modeling and Performance Validation - Hasan K.; Meraj S.T.; Othman M.M.; Lipu M.S.H.; Hannan M.A.; Muttaqi K.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bandpass filters; Harmonic analysis; Impulse response; Locks (fasteners); Low pass filters; Phase locked loops; Synchronization; Filter-based; Grid frequency; Harmonic elimination; Loop models; Loop performance; Low-pass filters; Model validation; Power harmonic filters; Savitzky-Golay filter; Synchronous reference frame; Transient analysis